Upaya Pengelolaan Sarana Pada Objek Wisata Air Soda di Desa Parbubu I Kecamatan Tarutung Kabupaten Tapanuli Utara - Terinus Wenda; Maringan Sinambela; Yulia KS Sitepu (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The Parbubu I soda water tourist attraction is one of the areas located in North Sumattra Province, Tarutung District, which is known as the Gospel tourism city, and also has the advantage of agricultural products such as yagung, sawa, coffee, and also has a variety of natural beauty and diversity. culture so that it can give rise to various potential tourist attraction destinations. Local communities also take the initiative to actively manage it into a potential tourist attraction. So tourist options are varied, and so are they. The Tourism Office in North Tapanuli district still has many problems that must be paid attention to, such as facilities, facilities for tourist visitors, in each tourist attraction destination location which are not yet adequate and still have not yet optimized management efforts, which still lacks professional human resources. Formulation The problem in this research is how to manage the facilities of a manager of the Parbubu I soda water tourist attraction, Tarutung District, as well as for the foundation of a researcher who wants to conduct research, in other tourist motorcycle taxi destinations and in their respective areas in North Tapanuli Province. The method used is a qualitative methodology which is descriptively oriented by having informants and also using data collection techniques, you can use observation techniques, interviews, document analysis. From this research, the researcher feels that the government of the tourism office and the district of Tarutung sub-district, and also especially the government of the village of Parbubu I, is establishing a cooperative relationship with the management of the Parbubu I soda water tourist attraction, because the management of the tourist attraction destination comes from the local community or is Individually, in terms of regional income, the Tarutung District Government has not implemented regulations so that tourism income goes into the coffers of a manager and Parbubu village or is distributed to the community who manages the soda water tourist attraction destination.